Molecular Mechanism of Proinflammatory Cytokine-Mediated Squamous Metaplasia in Human Corneal Epithelial Cells - Li, Shimin; Gallup, Marianne; Chen, Ying-Ting; McNamara, Nancy A. (Investigative ophthalmology & visual science, 2010)
The cornified envelope protein small proline-rich protein 1B (SPRR1B) is a biomarker for squamous metaplasia. Proinflammatory cytokines IL-1beta and IFN-gamma are potent inducers of ocular surface keratinization and SPRR1B expression. Here the molecular mechanisms controlling SPRR1B gene expression in response to IL-1beta and IFN-gamma are elucidated. A 3-kb fragment of the SPRR1B gene 5'-flanking region was amplified from human chromosome 1, sequentially deleted, and cloned into a luciferase vector. Constructs were transiently transfected into human corneal epithelial cells, and activity was assessed in response to IL-1beta, IFN-gamma, or basal medium. Functional cis-elements responding to IL-1beta and IFN-gamma were characterized by site-directed mutagenesis and gel mobility shift assay. Effects of mitogen-activated protein kinases p38, ERK, and JNK were assessed using inhibitors and dominant-negative mutants. Results were validated by real-time RT-PCR. The first 620 bp of the SPRR1B 5'-flanking region regulated constitutive expression and increased promoter activity in response to IL-1beta and IFN-gamma. Corresponding cis-elements for IL-1beta and IFN-gamma were bound by cAMP response element binding protein (CREB) and zinc-finger E-box binding homeobox 1 (ZEB1), respectively. Inhibition of p38 abolished the stimulatory effects of IL-1beta and IFN-gamma on SPRR1B, whereas inhibition of JNK and ERK had no effect. Dominant-negative mutants targeting p38alpha and p38beta2 blocked cytokine-induced SPRR1B promoter activity and mRNA expression. SPRR1B is upregulated by the proinflammatory cytokines IL-1beta and IFN-gamma via p38 MAPK-mediated signaling pathways that lead to the activation of transcription factors CREB and ZEB1, respectively. These results identify key intracellular signaling intermediates involved in the pathogenesis of immune-mediated ocular surface squamous metaplasia.